The ecological outlook of human development: acts and values contained in “Caritas in Veritate” - Orozco C., Richard (2010)
This article is an approach – from what the author understands as ecological rationale– to the  encyclical letter “Caritas in Veritate”, understanding the ecological rationale as the holistic approach of human development. Such perspective has allowed Pope Benedict XVI to over come one basic dichotomy of the scientific and economic philosophy, namely, the fact-value dichotomy.  In his encyclical letter, the Pope criticizes the concept of development that the contemporary world seeks to impose, thus acknowledging that it finds its grounds on making a differentiation of human levels. The result is a moral crisis creeping into a world that achieves significant advances in science and economy, contradictions that clearly evidences the erroneous understanding of the dichotomy.